A Qualitative Approach to Understanding the Holistic Experience of Psychotherapy Among Clients - Seow, Lee Seng Esmond; Sambasivam, Rajeswari; Chang, Sherilyn; Subramaniam, Mythily; Lu, Huixian Sharon; Assudani, Hanita Ashok; Tan, Chern-Yee Geoffrey; Vaingankar, Janhavi Ajit (Frontiers in Psychology, 2021)
Background: The study of client experience across multiple service encounters (or touchpoints) is important from a service research perspective. Despite availability of effective psychotherapies, there exists a significant gap in the optimal delivery of such interventions in the community. This study therefore aimed to explore client experience of psychotherapy by integrating before-during-after service encounters using a qualitative approach. Methods: 15 clients of outpatient psychotherapy were interviewed and data saturation was reached. Topics included pathways and reasons to seeking psychotherapy, aspects of therapy process that have been helpful or unhelpful, and perceived change after receiving psychotherapy. Information were analysed using inductive thematic analysis method. Emergent themes pertaining to pre-psychotherapy encounter were mapped onto major components identified in the Andersen’s Health Service Utilisation Model. Results: Mental health stigma and the lack of understanding about psychotherapy were predisposing factors that impeded service use while preference for non-pharmacological intervention promoted its use. Enabling factors such as affordability and service availability were also of concern, along with perceived and evaluated needs. Therapists’ attributes and techniques application, and client resistance were found to impact therapeutic alliance. While majority experienced positive change or had engaged in self-help strategies after receiving psychotherapy, others cited limited impact on symptoms recovery or problematic self-coping without the therapists. Conclusions: Our study proposed to expand on the Andersen’s Behavioral Model to include therapy-related factors so as to provide a more holistic understanding of client use of psychotherapy. More importantly, the study identified several barriers to access and negative experiences or outcomes, which should be addressed to promote uptake of the psychotherapy intervention.